RECEPTION WITH RISK CLASSIFICATION: CHARACTERISTICS OF THE DEMAND IN AN EMERGENCY UNIT - Vanessa Carolina Grigini Godoi; Gabriela Schiavon Ganassin; Kelly Cristina Inoue; Nelly Lopes de Moraes Gil (Universidade Federal do Paraná, 2016)
This study aimed to characterize the care of users with the guideline for Reception with Risk Classification in an Emergency Unit of Paraná state. This descriptive, exploratory and quantitative field study used 500 medical records of patients treated between January and May 2014 as the source of information, obtained by simple random sampling. Demographic and clinical data, related to the care network and risk classification, were collected and submitted to descriptive statistics. The majority of the patients were women, from 20 to 29 years of age, of spontaneous demand; referred by nurses and Primary Health Units. Regarding the classification of risk, four (0.8%) were emergency, 175 (35%) more urgent, 245 (49%) less urgent and 68 (13.6%) non-urgent; with the nursing technician mainly performing the triage and discharge being the primary outcome. There is a need to improve the medical records and review the classification process for clarification of specific failures.